Implementasi Actuating Prinsip-Prinsip Manajemen Pendidikan Islam dalam Perspektif Hadis di SMP Karya Pertiwi - Putri, Rizky Ananda; Khoriroh, Fitri; Aspandi, Aspandi; Bachtiar, Machdum (Jurnal Ilmiah Wahana Pendidikan, 2024)
SMP Karya Pertiwi is one of the educational institutions that has a hidden Islamic curriculum. In practice, these management principles need systematic application.The principles in Islamic education management include faith and morals, deliberation, justice and equality, division of work and tasks, guided by management functions, cooperation and sincerity The aim of this research is to analyze the process of implementing the principles of Islamic education management from a hadith perspective at SMP Karya Pertiwi. This method used in this research is qualitative with a case study method. To find out the extent of the process of implementing the principles of educational management. Meanwhile for data collection, the process of interview observation and documentation was used. The result of this research are not yet fully effective in implementing educational management principles in the form of justice and solidarity. So, further follow-up is needed to ensure the continuity of education management in SMP Karya Pertiwi